Biodiesel in Brazil: An analysis of production, consumption, and prospects in the energy transition (Research, Society and Development, 2023)
Humanity depends on the generation and transformation of the energy for its maintenance and development. Considering the methods of energy generation, the ones using nonrenewable sources, like petroleum, are the most used and economically viable. For many years, the energy generation was an extractive action, which did not consider the effects that this mode of production would have on the environment in the long term. However, in recently years, much has been discussed about the importance of product energy in an environmentally friendly way, and renewable sources have gained great attention for presenting fewer risks to the environment. In this context, biodiesel has proven to be viable and a very promising alternative in contrast with the diesel provided by petroleum extraction, that reduces the pollutants gases and the ones linked to the global warming. Furthermore, biodiesel is an important instrument of social transformation, because its production can make use of raw materials produced by farmers engaged in family-based agriculture, thereby inserting these groups in the economic matrix. This article aims to analyze the demands for the production, consumption, and perspectives of biodiesel in Brazil based on a qualitative narrative review of the state of the art in the production, consumption, and use of this biofuel. It aligns environmental, social and governance aspects that has been incessantly debated due to climate changes and projections of petroleum reserves depletion.